Storage Of Documents For The Process Of Educators By Utilizing Digital Media (Khairun University Case Study) - Samad, Abjan; Albaar, Muhammad Ridha; Sudjud, Nuryati; Sitanggang, Rinson (Akademi Ilmu Komputer Ternate, 2024)
Abstract: In an agency, document (archive) management is a very crucial aspect in supporting various work activities. The success of this management depends on the ability to organize and store documents efficiently. By carrying out good management and storage, employees can easily find copies of original documents needed to support various work activities. The types of documents that are generally managed in companies or agencies include recordings, writing, and various other media. The scope of the research begins with the aim of exploring and analyzing the impact of using digital media so that it can create a digital-based document repository. The approach applied in this research is the prototype development method, a systematic approach to achieve innovation and development. The current system shows that the process of proposing documents for promotion to staff at UNKHAIR is still done manually, that is, all files are collected in hardcopy to the faculty and then verified and submitted to the personnel department for an assessment process by the personnel department. This proposed system is designed to overcome problems that arise from the current system, which has been created by researchers. a digital storage medium to make existing staff easier so that all files can be uploaded whenever and wherever they are and minimize loss or scattered files. The results of this research utilize Google Drive and QR Code which is the right solution to overcome the problem of storing digital archives that are less organized and difficult. accessed, Google Drive can be used to improve archive management skills.Kata kunci: Google Drive, Tendik, Archive storage, Prototype, QR Code